Pajak hotel di Kabupaten Ende: trend, efektivitas dan kontribusi terhadap pajak asli daerah - Arif Triwinarso; Susianti Susianti; Maria Giovani Putri Leda (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
Hotel tax is one source of local taxes that will contribute to the potential local revenue (PAD) if managed effectively and can be a source of funding for regional development. The purpose of this study was to determine the trend of realization, the level of hotel tax effectiveness, and its contribution to local taxes and PAD in Ende Regency for the period 2017 - 2020. The research method used was descriptive quantitative with secondary data as the data source. The data was obtained from the Regional Revenue Agency of Ende Regency. The results of the study show that in general, the trend of hotel tax revenue realization and effectiveness has decreased. This is caused by internal factors such as a very high target increase without taking into account the existing potential as well as several external factors such as a low level of public awareness and knowledge. The effectiveness of hotel tax revenue in Ende Regency 3 out of 4 years of observation is in the ineffective category (< 60%). The contribution of hotel taxes to local taxes and Ende Regency's Original Revenue is relatively very small. The factors that cause the hotel tax to be ineffective are the lack of knowledge and awareness of citizens towards taxation, tax management accountability that is not optimal, payments are not by the value they should be, submission of SPTDP not on time, and some taxpayers close their business without notification.